Competency-based interprofessional education enhances collaboration skills in special education and speech-language pathology students - Holman, Katherine Cullinan; Wilson, Kaitlyn P.; Knollman, Greg; Russell, Arlene (Frontiers in Education, 2025)
IntroductionThere is growing emphasis on the importance of interprofessional education and practice when supporting autistic students and their families. However, implementation of hands-on interprofessional, collaborative training models are limited in research and practice. This study examined the impact of a hands-on, competency-based interprofessional, supplemental training course (part of a two-year interprofessional training program, “Project LINC”) for special education and speech-language pathology graduate students (n = 21). To determine the effectiveness of intentionally designed interprofessional collaborative learning strategies used during the course, this study addressed three main objectives: (1) to evaluate how the course affected students’ progress toward meeting the Project LINC competencies; (2) to examine how students implemented collaboration strategies learned during the program; and (3) to identify what students gained from the clinical experience and how it contributed to their ability to collaborate effectively.MethodsA mixed methods approach was used to evaluate the impact of a hands-on clinical interprofessional education (IPE) course on students’ competencies and collaboration skills through quantitative self-ratings, paired t-tests, and effect size calculations, as well as qualitative analysis of students’ reflections using reflective thematic analysis. Student survey data, simulation ratings, and written reflections were analyzed by trained coders to identify themes and ensure reliability in understanding students’ collaborative development.ResultsThe study found that students reported significant perceived gains across all Project LINC competencies after completing a hands-on clinical IPE course, with statistically significant improvements on all self-rated items and large effect sizes. In simulated interprofessional meetings, students rated themselves as highly proficient collaborators. Qualitative analysis of student reflections revealed that the course strengthened their collaborative actions, problem-solving skills, use of communication tools, and professional dispositions such as flexibility, empathy, and trust.DiscussionThe findings from this study point to key traits that can help students overcome real-world barriers to collaboration and build meaningful interprofessional partnerships. Implications and suggestions for practice are discussed.